Essential oils and oleoresins : a study of selected producers and major markets - International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre UNCTAD/GATT, 1986)
This is astudy of supply position of selected major producers of, and trends in major markets for, essential oils and spice oleoresins. Part 1 describes origins, uses, production and main markets for over 50 products. Part 2 contains brief descriptions of the essential oils and spice oleoresin industries in 18 producing countries. Part 3 presents the main trends in demand in USA, Canada, Western Europe and Japan. Part 4 reviews trade structures and practices. It also includes appendices which provides statistical data and list importers, dealers, merchants, and processing and compounding houses.
lje 22/1/19
Loans
Keywords: Essences and essential oils industry; International trade; Oleoresin industry